Prevalensi Dan Distribusi Tingkat Gejala Depresi Pada Lansia Di Wilayah Komunitas Rw 14 Citeureup - Elisa Adelia do Carmo; Judika Rubi Marta Sirait; Rahmi Imelisa; Fifi Siti Fauziah Yani; Khrisna Wisnusakti; Astri Permatasari (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
Background: Depression is a common mental health problem among older adults and contributes to decreased quality of life, increased morbidity, and higher health care utilization. In community settings, depressive symptoms are often under-detected due to limited screening and the assumption that psychological changes are a normal part of aging. Objective: This study aimed to describe the prevalence and distribution of depressive symptom levels among older adults living in RW 14 Citeureup community area. Methods: This study employed a descriptive quantitative design with a cross-sectional approach. A total of 44 older adults were recruited using total sampling. Data were collected using the Geriatric Depression Scale (GDS). Univariate analysis was performed to describe respondent characteristics and the distribution of depressive symptom levels. Results: Most respondents were aged 66–84 years (54.5%) and female (56.8%). Based on GDS scores, the majority experienced mild depression (70.5%), followed by moderate depression (25.0%) and severe depression (4.5%). Conclusion: The prevalence of depressive symptoms among older adults in RW 14 Citeureup community area was relatively high, with mild depression as the dominant category. Routine community-based mental health screening is essential for early detection and prevention of depression progression among older adults.